Predictive value of serum cystatin C for morbidity and prognosis of acute kidney injury in patients with acute coronary artery syndrome - LIU Hui-lan; LI Xiao-ning; FU Shuai; HU Yu-gang; WAN Jing (Linchuang shenzangbing zazhi)
Objective To investigate the relationship of serum cystatin C(sCysC) levels with the morbidity and mortality of acute kidney injury(AKI) in patients with acute coronary artery syndrome(ACS). Methods The clinical data from 268 patients with ACS, admitted to the coronary care unit of Zhongnan Hospital of Wuhan University from January 1, 2014 to June 1, 2015, were analyzed. Based on the diagnostic and staging criteria for AKI from KDIGO(Kidney Disease:Improving Global Outcomes), these ACS patients were classified into two groups: non-AKI group and AKI group, Clinical features, and laboratory data were compared between the two groups, Multivariate logistic regression analysis was used to analyze the independent risk factors for the morbidity of AKI and a COX proportional hazards regression model was used to estimate the risk factors of all-cause mortality and prognosis in ACS patients. Moreover, the subject working characteristic curves were plotted to assess the predictive value of sCysC for morbidity and the prognosis of AKI in patients with ACS. Results Of the 268 patients, 89(33.2%) experienced AKI,(17.5% of them had phase 1 AKI, 9.3% had phase 2 AKI, 6.3% had phase 3 AKI). Multivariate logistic regression analysis showed, sCysC(OR=3.920, 95%CI 2.216～6.936, P<0.01) was an independent risk factor for AKI morbidity in ACS patients. COX survival regression analysis showed, sCysC was an independent risk factor for the hospitalization mortality and 2-year mortality of AKI in ACS patients(HR=1.385, 95%CI 1.014～1.890, P<0.05; HR=1.972,95%CI 1.626～2.393,P<0.01). Conclusions sCysC is a good independent predictor for morbidity and prognosis of AKI in patients with ACS.